2021
DOI: 10.1186/s13018-021-02460-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonication in the diagnosis of fracture-related infections (FRI)—a retrospective study on 230 retrieved implants

Abstract: Background In fracture-related infections (FRI), both the diagnosis of the infection and the identification of the causative pathogen are crucial to optimize treatment outcomes. Sonication has been successfully used for periprosthetic joint infections (PJI); however, its role in FRI remains unknown. Our aim was to determine the diagnostic accuracy (sensitivity, specificity) of sonicate fluid culture (SFC). The primary objective was to compare SFC with peri-implant tissue culture (PTC) overall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Aside from TSC, new emerging techniques have recently been developed, also aimed at increasing the detection rate of FDRI-associated microorganisms. Based on a retrospective analysis of 230 cases, Bellova et al ( 7 ) found that sonicate fluid culture might be a useful adjunct in diagnosis of FDRI, especially for low-grade infections. Outcomes of an updated meta-analysis revealed that traditional tissue sampling was more sensitive while sonication fluid sampling was more specific, and, thus, the authors suggested the integration of both methods to obtain optimal results ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from TSC, new emerging techniques have recently been developed, also aimed at increasing the detection rate of FDRI-associated microorganisms. Based on a retrospective analysis of 230 cases, Bellova et al ( 7 ) found that sonicate fluid culture might be a useful adjunct in diagnosis of FDRI, especially for low-grade infections. Outcomes of an updated meta-analysis revealed that traditional tissue sampling was more sensitive while sonication fluid sampling was more specific, and, thus, the authors suggested the integration of both methods to obtain optimal results ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the positive rate of culture is not high ( 6 ). In order to increase the positive rate, different adjunctive strategies had been introduced, such as sonicate fluid culture ( 7 ) and intramedullary tissue culture ( 8 ).…”
mentioning
confidence: 99%
“…Recently, different adjunctive strategies for pathogen identification were reported, aiming at increasing the detection rate. Bellova et al [ 55 ] reported the efficiency of sonication in the diagnosis of FRI, and outcomes of 230 retrieved implants revealed that sonication of fracture devices may be a useful adjunct for FRI. In a meta-analysis focusing on the diagnostic accuracy of sonication fluid aspiration for FRI, Ahmed et al [ 56 ] reported that the sensitivity and specificity of the sonication method were 86% and 98%, with the tissue sample culture as 98% and 38%, respectively.…”
Section: Diagnosismentioning
confidence: 99%